Re-diseño en el desarrollo y aplicación de un envase corrugado parafinado para uso en exportación de mango - Alarcón, Angel (2010)
Graduation Project was subject matter is to discuss the development and implementation of the Re - Design of a corrugated cardboard box used as a Container - Packing for the Exporter RICABERTO SA that markets handle the customer requested a change in the design of the box currently being used, keeping the overall dimensions and the test (composition of paper), to diminish the number of units of standard size fruit per unit carton. The aim is to reduce the interior volume and keep the box with the same cost. Once the design tests, we got a box with the same external measures, lower volume and as an added value making the most of space on the sheet of cardboard, reducing its waste by 8% in addition to the Re - design was improved the strength of the box stacking increasing the value of 19 to 20 levels. For the development of this Re - Design Vector were used Word software that performs design grids for twodimensional drawings, The Impact program that performs simulation grids and planes in three dimensions, the machine that produces prototypes Sample Maker based on the designs made in the above programs, thus achieving an overpack container will be tested at customer sites to determine their feasibility. In addition, tests of endurance and stacking allowed to certify that the container-corrugated cardboard packaging can be stacked in greater numbers, which means a gain of space in warehouses and export volume of the customer. Keywords: Test, Calibre, Vector Work, Impact